Edukasi Laktasi Meningkatkan Praktek Pemberian ASI Eksklusif pada Primipara - Dinda Puspita Ramadhani; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Mother's Milk (breast milk) exclusive breastfeeding was only in babies starting at the age of 0 to 6 months. When mothers don't know how to manage their lactation, it can stop them from breastfeeding their babies properly. The goal of this study is to find out what happens when people learn how to breastfeed and how that changes the practice of exclusively breastfeeding in first-time moms. The quasi-approach and experimental pre-post strategy are used in this study. Mothers who had their first child at the Bangetayu health center made up the sample, which was made up of 50 people chosen at random from the whole population. Questionnaires filled out before and after the activity were used to collect data. The 50 people who filled out the Wilcoxon test showed that mothers' knowledge, attitudes, and skills were different before and after education. The p value of 0.001 (p value <0.05) means that mothers' knowledge, attitudes, and skills on exclusive breastfeeding were different before and after education. Lactation instruction had an effect on the practice of nursing exclusively for the first six months after giving birth.